A novel lysin Ply691 exhibits potent bactericidal activity against Streptococcus suis - Shang, Yanhong; Li, Xinyi; Ren, Shihang; Du, Congyang; Schwarz, Stefan; Li, Chenglong; Du, Xiang-Dang (Frontiers in Veterinary Science, 2025)
IntroductionStreptococcus suis represents a growing zoonotic pathogen, exacerbated by increasing antimicrobial resistance due to a widespread and often inappropriate antimicrobial use. This escalating challenge underscores the pressing need for innovative treatment strategies against streptococcal infections in pigs. In our study, we identified Ply691, a prophage-encoded lytic enzyme.MethodsThe corresponding gene was identified during whole genome analysis of S. suis SC267. Structural domain analysis revealed that Ply691 consists of an N-terminal Amidase-5 catalytic domain, a C-terminal Glucosaminidase catalytic domain, and two centrally located CW-7-binding structural domains. In order to investigate the bactericidal potential of Ply691, an in vitro bactericidal assay was conducted using Ply691, and its bactericidal effect was evaluated by colony counting method after applying it to different strains of bacteria and at different temperatures and pH conditions. Subsequently, a mouse bacteremia model was established, and the in vivo bactericidal efficacy of Ply691 was evaluated by measuring the bacterial residues in the blood and different organs of mice treated with Ply691.ResultsIn-vitro antimicrobial susceptibility testing demonstrated that Ply691 exhibits potent lytic activity against 11 serotypes of S. suis, including serotypes 2, 3, 5, 9, 10, 12, 17, 18, 19, 29, and 30. Furthermore, Ply691 reduced the number of S. suis colonies by approximately 1 log within 20 min. Ply691 also displayed a broad temperature adaptability range (4°C-37°C) and remarkable alkaline tolerance (pH 7-10). In an in vivo murine bacteremia model, Ply691 demonstrated significant therapeutic effects. Administration of Ply691 at a dose of 2 mg per mouse by intraperitoneal injection an hour post-infection resulted in a 100% survival rate and substantially reduced the bacterial load in the blood and various organs (heart, liver, spleen, lung, kidney, and brain). Histological analysis confirmed that these organs closely resembled those of the control group.DiscussionPly691 exhibits broad-spectrum lytic activity against S. suis with unique structural advantages. It demonstrates robust efficacy in vivo without inducing resistance, showing significant therapeutic potential for streptococcal infections.